The Elements of Civil Peace with Non-Muslims in the Prophetic Curriculum - Obaid Al Shuwaikh, Assist. Prof. Dr. Khalid Amer (Opción)
The people of Dhimma, covenant, truce and safety are terms that Muslim scholars call non-Muslims, residents or immigrants to The Land of Islam, and that they are in the era of Muslims, their sin and their protection. Civil peace towards others does not mean at all the contractual and intellectual thaw towards the other and the loss of identity, humiliation and rebuttal to it, but rather mutual respect and knowledge of each party’s money and what it is. The policy of civil peace in the Prophetic curriculum, which provided the Islamic call and the prophetic leadership with a good reputation, and a bright face in front of public opinion, which helped to spread Islam, and the popularity of the people.